7th Cambridge Diagenesis Conference 2011: an introduction. (April 2014) - Jeans, C. V.; Tosca, N. J.
Abstract : The Cambridge Diagenesis Conferences (1981–1998) were set up to act as a conduit for the interchange of clay mineral expertise between universities and research institutes on one hand, and the hydrocarbon industry on the other. At the time, oil companies were dealing with the development of the North Sea Oil Province which was turning out to be a natural laboratory for the fundamental study of authigenic clay minerals and their relationship to lithofacies, burial, overpressure, reservoir quality and hydrocarbon emplacement. This symbiosis between industry and academia flourished for nearly two decades. Each conference was followed by a special issue of Clay Minerals dealing with topics relevant to, or discussed at the particular meeting. By the late 1990s the North Sea had become a mature province and the major oil companies were looking to other parts of the world to replenish their reserves.